2013
DOI: 10.3390/ijms141223454
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Conservation of the Prespa Trout in the Balkans

Abstract: The Balkans are known to have a high level of biodiversity and endemism. No less than 15 taxa have been recorded in salmonids of the Salmo genus. Among them, the Prespa trout is found in only four river systems flowing into Lake Macro Prespa, three in the Former Yugoslav Republic of Macedonia and one in Greece. This is the first comprehensive survey of all streams located within the Macro Prespa Basin, encompassing the whole taxon range. A large genetic sample of 536 Prespa trout was collected mainly between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…trutta (Pujolar et al , ). Similar heterozygosities ( H O = 0·16–0·35) have been observed in the Prespa trout Salmo peristericus Karaman 1938 in Macedonia (Berrebi et al , ), another endangered salmonid as a result of anthropogenic factors including reintroductions. The low heterozygosities found in the threatened S .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…trutta (Pujolar et al , ). Similar heterozygosities ( H O = 0·16–0·35) have been observed in the Prespa trout Salmo peristericus Karaman 1938 in Macedonia (Berrebi et al , ), another endangered salmonid as a result of anthropogenic factors including reintroductions. The low heterozygosities found in the threatened S .…”
Section: Discussionsupporting
confidence: 66%
“…While Italian S. marmoratus populations are not experiencing floods, they are subjected to the negative effect of introgression with S. trutta (Pujolar et al, 2011a). Similar heterozygosities (H O = 0⋅16-0⋅35) have been observed in the Prespa trout Salmo peristericus Karaman 1938 in Macedonia (Berrebi et al, 2013), another endangered salmonid as a result of anthropogenic factors including reintroductions. The low heterozygosities found in the threatened S. peristericus and S. marmoratus (this study) contrast with the microsatellite heterozygosity values generally found in salmonids, ranging between 0⋅6 and 0⋅8 (Hansen et al, 2002;Jensen et al, 2005;Serbezov et al, 2008).…”
Section: Discussionmentioning
confidence: 71%
“…Berrebi et al, 2013;Gratton, Allegrucci, Sbordoni & Gandolfi, 2014;Maric, Bajec, Schoffmann, Kostov & Snoj, 2017 and references therein). Berrebi et al, 2013;Gratton, Allegrucci, Sbordoni & Gandolfi, 2014;Maric, Bajec, Schoffmann, Kostov & Snoj, 2017 and references therein).…”
Section: Introductionunclassified
“…probably have a trans-Apennine origin due to their genetic similarity with haplotype ADcs11 (see Fig. 2), 346 this latter being very common in the Adriatic region Berrebi et al, 2013). 347 diversity of more western origin (AD-Tyrrh1, 2 and 4).…”
mentioning
confidence: 99%